Using Pesticides on Your Pet - Frederick M. Fishel (EDIS, 2019)
Some products considered to be safe for pets have been relabeled to enhance safety. This document is PI-82, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date November 2005.